Risco reputacional em frigoríficos de carne bovina da amazônia brasileira - Galuchi, Tharic Pires Dias (2018)
The relevance of the beef chain to the Brazilian economy has increased in the last two decades. This growth has been accompanied by the advance of cattle production and agro-industries to areas located within the Legal Amazon. The impacts of this displacement have been contested by stakeholders. These actors attribute to the beef supply chains originating in that region a set of negative social and environmental repercussions. On reaction of the slaughterhouses in response to this challenge is the implementation of risk management systems that mitigate possible damage to their reputations caused by the publicizing of the possible deleterious effects of their activities. In this context, this study aims to analyze how the slaughterhouses in the Amazon region identify socio-environmental factors of suppliers that have the potential to raise their reputational risks and also the strategies used to mitigate these risks. For that, a qualitative exploratory study was developed through a multiple case study. The results showed that risk factors are largely established in public commitments negotiated with stakeholders. Deforestation, invasion of indigenous lands, work analogous to slavery and destruction of protected areas are the most cited factors as reputational risk generators. As risk mitigation strategies, the slaughterhouses maintain socio-environmental assessment practices of all their suppliers through a system of registry verification of the existence of infractions in the farms. Verification system auditing and reporting to the stakeholder are also used. The mitigation strategy of avoiding the risk changing supplier is more frequent. Other forms of mitigation are also observed, but it is noted that the risk is accepted when the stakeholders' perception indicates that the slaughterhouses are not responsible for livestock irregularities.